New Type of Donor-Acceptor Through-Space Conjugated Polymer - Lin Lin; Yasuhiro Morisaki; Yoshiki Chujo (International Journal of Polymer Science)
We report the synthesis and properties of a novel through-space conjugated polymer with a [2.2]paracyclophane skeleton. The obtained polymer possessed donor (fluorene) and acceptor (2,1,3-benzothiadiazole) segments that were alternately π-stacked in proximity via the [2.2]paracyclophane moieties. The good overlap between the emission peak of the donor unit (fluorene) and the CT band of the acceptor unit (2,1,3-benzothiadiazole) caused fluorescence resonance energy transfer, and the visible green light emission from the acceptor unit was observed.